Development of a graphical user interface to calculate semiconductor energy band diagrams - Yang, Ting (Nanyang Technological University, 2020)
This is a simple, convenient and workable user interface, designed from the perspective of user. It’s mainly developed using Python 3.8 and PyQt5. Guided type dialog window allows users to input required parameters, and then combines with external DLL files to output a satisfactory band diagram. The interface consists of two toolbars, three display windows, and two workstation file trees. This thesis mainly explains the process of developing a graphical user interface using Python 3 and PyQt5, and how to call DLL files. The developed software will be helpful to design semiconductor devices and teach semiconductor physics courses.